Efficacy of combined interferon alpha and long-term lamivudine therapy in children with chronic hepatitis B - Kuloğlu, Zarife; Kansu, Aydan; Erden, Esra; Girgin, Nurten (The Turkish Journal of Pediatrics, 2010)
The aim of this study was to evaluate the efficacy of interferon alpha (IFN-alpha) and long-term lamivudine therapy in children with chronic hepatitis B and to determine the optimal duration of lamivudine therapy. Thirty-eight HBeAg-positive children simultaneously received IFN-alpha2a 5 MU/m2 to 10 MU/m2 for six months and lamivudine (4 mg/kg/day). Lamivudine was administered until anti-HBe seroconversion and was continued for six months in responders. During the five-year study period, we evaluated the efficacy of treatment, occurrence of YMDD mutants and adverse effects. During the study period, alanine aminotransferase (ALT) normalization, clearance of hepatitis B virus (HBV) DNA, HBeAg/anti-HBeAb, HBsAg/anti-HBsAb seroconversion, and histological response were noted in 27 (71.1%), 14 (36.8%), 13 (34.2%), 2 (5.2%) and 10 (47.9%) patients, respectively. Complete response was determined in 34.2% (13/38), and in 69.2% of these responders, response was achieved within 18 months. Breakthrough and YMDD mutant rates were 65.8% and 55.2%, respectively. Breakthrough time was a median 24 months and was associated with low baseline ALT level (p < 0.01). In conclusion, although lamivudine was used for a longer period, the response rate was not higher than in previous reports. We suggest that 18 months’ duration of lamivudine treatment is sufficient for combination therapy.